CORPORATE GOVERNANCE AND MAQASID SHARIA PERFORMANCE ON ISLAMIC BANKS IN INDONESIA - Sulistiawati Sulistiawati; Annisa Fithria (Tasharruf: Journal Economics and Business of Islam, 2021)
The implementation of good corporate governance (GCG) can be seen in the relationship between the main elements of GCG mechanisms implemented by the board of commissioners (BOC) as supervisors, the board of directors (BOD) as managers, and the sharia supervisory board (SSB) as directors, consultants, and supervisors on sharia compliance of Islamic banks. This study aims to analyze the effect of corporate governance on the maqasid sharia-based performance of Islamic banks (Bank Umum Syariah–BUS) in Indonesia from 2016 to 2019. Corporate governance is proxied by the number of BOC, BOD, the audit committee, and SSB. Based on the purposive sampling criteria, 8 BUS are used as samples in this study, with a total of 32 observations. The type of data used is secondary data in the form of annual reports and GCG reports. The data analysis technique used is multiple regression analysis. The results show that BOC has a negative effect on the maqasid sharia-based performance of Islamic banks. In contrast, BOD positively impacts the maqasid sharia-based performance of Islamic banks. On the other hand, the audit committee and SSB do not affect the maqasid sharia-based performance of Islamic banks.